Risk Factors and Predictors of Adverse Outcomes in Twin Pregnancies: A Review - Biaobiao Wang; Weishe Zhang; Yiran Fu; Qi Wang; Yanying Wu; Jia Nie; Lijuan Liu; Xiaowen Zhang; Hongtao Zeng; Jingrui Huang (IMR Press, 2024)
Objective: Twin pregnancies are associated with a higher risk of adverse pregnancy outcomes than are singleton pregnancies. Although the risk factors and predictors of adverse outcomes in singleton pregnancies have been clearly identified in numerous studies, those specific to twin pregnancies remain less consistent. This study was performed to summarize and evaluate the risk factors and predictors of adverse outcomes in twin pregnancies. Mechanism: A comprehensive review was conducted using the PubMed and Web of Science databases to analyze and identify the relevant risk factors and predictors of avderse outcomes in twin pregnancies. Findings in Brief: The risk factors and predictors of adverse outcomes in twin pregnancies are largely similar to those in singleton pregnancies, particularly in relation to preeclampsia and preterm birth and especially for conditions not unique to twin pregnancies. However, there remains a gap in the study of complications specific to twin pregnancies, largely because of their chorionicity. Conclusions: Early identification of risk factors and predictors for adverse outcomes in twin pregnancies facilitates earlier prevention and intervention and lead to improved management of serious complications in twin pregnancies.